Toxicidade financeira experienciada por mulheres com câncer: pesquisa qualitativa - Beatriz Jorge Oliveira Gomes; Gláucia Maria Canato Garcia; Eloah Boska Mantovani; Patricia Chatolov Ferreira; Luciana de Alcantara Nogueira; Sonia Silva Marcon (Online Brazilian Journal of Nursing, 2026)
Objective: To understand how financial toxicity is manifested and interferes in the life of women with cancer. Method: A descriptive-exploratory research study of a qualitative nature, conducted with female cancer survivors. The data were collected between May and September 2025 by means of semi-structured interviews that were audio-recorded after due authorization. Subsequently, the data were subjected to content analysis, in its thematic modality. Results: The participants were 24 women who had already finished their primary treatments. Four categories emerged from the data analysis. These categories show that, even if enjoying access to the Unified Health System or to health plans, the participants faced high costs related to medications, differentiated eating, commuting, tests and complementary therapies during their treatments, in addition to reduced incomes due to having be distanced from their work for a specific period of time, sometimes even depending on support networks for financial issues. These findings show that financial toxicity permeates economic, emotional and social dimensions, exerting impacts on autonomy and well-being. Conclusion: It is fundamental to acknowledge the magnitude of financial toxicity during cancer treatments and to include it in care plans, in addition to sensitizing managers about the importance of implementing policies that expand the financial protection offered to the patients.